Mrs Lirriper - Dickens, Charles, 1812-1870 [et al.] (London Hesperus Classic, 2005)
Contains short stories by Elizabeth Gaskell, Amelia Edwards, Charles Collins (Wilkie Collins's brother) and other Victorian writers. Published for the first time in 1863-64 in a Christmas Special to Household Worlds, 'Mrs Lirriper's Lodgings' and 'Mrs. Lirriper's Legacy'. Recently widowed, Mrs. Lirriper devotes her energies to attending to the needs of her assorted lodgers. But when a newborn child is abandoned to her care, her responsibilities extend to new levels. Enlisting long-time lodger, the Major, into the role of 'guardian', the two develop an increasing affection for the boy. In an effort to entertain the growing lad, they relate the stories of their fellow-lodgers, little knowing that they are about to embark on their own real-life tale of impending death, guilty secrets and mysterious legacies
Include Notes and Bibliographical Note
Keywords: Lodging-houses -- England--London -- Social conditions